STUDENTS’ EXPERIENCES IN USING PODCASTS TO ENHANCE ENGLISH LISTENING COMPREHENSION - Elita Febrianti; Yustika Nur Fajriah; Wahid Hasim (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
In order to comprehend spoken language and effectively engage in communication, listening is a crucial English language acquisition ability. However, a lack of exposure to real listening materials, new terminology, and pronunciation variations make it challenging for many English as a Foreign Language (EFL) learners to comprehend spoken English. Podcasts have become a popular educational tool that offers meaningful listening experiences and real listening input. The purpose of this study is to investigate how students use podcasts to improve their listening comprehension of English. This study used a qualitative descriptive design. Five pupils from a secondary school in Garut, West Java, Indonesia, took part. Semi-structured interviews and classroom observations were used to gather data. The interactive model put forth by Miles and Huberman, which includes data reduction, data display, and conclusion drawing, was used to examine the data. The findings revealed four major themes: podcasts enhanced students’ listening comprehension, podcasts created enjoyable learning experiences, students encountered challenges during podcast listening activities, and podcasts increased students’ confidence in learning English. The findings indicate that podcasts provide meaningful listening exposure that supports listening development while creating a more engaging learning environment. Although students experienced difficulties related to unfamiliar vocabulary and pronunciation, they generally perceived podcasts as beneficial for improving listening comprehension. Therefore, podcasts can be considered an effective learning medium for supporting English listening instruction in EFL classrooms. ABSTRAK Untuk memahami bahasa lisan dan terlibat secara efektif dalam komunikasi, mendengarkan merupakan kemampuan penting dalam pemerolehan bahasa Inggris. Namun, kurangnya paparan terhadap materi mendengarkan yang sebenarnya, terminologi baru, dan variasi pengucapan membuat banyak pembelajar Bahasa Inggris sebagai Bahasa Asing (EFL) kesulitan memahami bahasa Inggris lisan. Podcast telah menjadi alat pendidikan populer yang menawarkan pengalaman mendengarkan yang bermakna dan masukan mendengarkan yang nyata. Tujuan penelitian ini adalah untuk menyelidiki bagaimana siswa menggunakan podcast untuk meningkatkan pemahaman mendengarkan bahasa Inggris mereka. Penelitian ini menggunakan desain deskriptif kualitatif. Lima siswa dari sebuah sekolah menengah di Garut, Jawa Barat, Indonesia, berpartisipasi. Wawancara semi-terstruktur dan observasi kelas digunakan untuk mengumpulkan data. Model interaktif yang dikemukakan oleh Miles dan Huberman, yang mencakup reduksi data, tampilan data, dan penarikan kesimpulan, digunakan untuk memeriksa data. Temuan mengungkapkan empat tema utama: podcast meningkatkan pemahaman mendengarkan siswa, podcast menciptakan pengalaman belajar yang menyenangkan, siswa menghadapi tantangan selama kegiatan mendengarkan podcast, dan podcast meningkatkan kepercayaan diri siswa dalam belajar bahasa Inggris. Temuan menunjukkan bahwa podcast memberikan paparan mendengarkan yang bermakna yang mendukung pengembangan kemampuan mendengarkan sekaligus menciptakan lingkungan belajar yang lebih menarik. Meskipun siswa mengalami kesulitan terkait kosakata dan pengucapan yang tidak familiar, mereka umumnya menganggap podcast bermanfaat untuk meningkatkan pemahaman mendengarkan. Oleh karena itu, podcast dapat dianggap sebagai media pembelajaran yang efektif untuk mendukung pengajaran mendengarkan bahasa Inggris di kelas EFL.